2021
DOI: 10.1002/aah.10130
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Bacteriophages and Immunological Monitoring for the Treatment of a Case of Chronic Septicemic Cutaneous Ulcerative Disease in a Loggerhead Sea Turtle Caretta caretta

Abstract: In this case study, phage therapy was applied to treat a multidrug‐resistant case of septicemic cutaneous ulcerative disease (SCUD) caused by Citrobacter freundii in a loggerhead sea turtle Caretta caretta. Phages were applied topically, intravenously, into the carapace, and into the exhibit water using various phage cocktails specific to the causative agent over an 8‐month period. This was performed in conjunction with antimicrobial therapy. The animal was monitored through weekly cultures, photographs, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…Bacteriophages, as a non-antibiotic technique for treating bacterial infections, have recently gained popularity. They have been used successfully in humans and other animal species [ 9 , 10 ]. Compared to antibiotics, bacteriophages have a completely different antibacterial mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriophages, as a non-antibiotic technique for treating bacterial infections, have recently gained popularity. They have been used successfully in humans and other animal species [ 9 , 10 ]. Compared to antibiotics, bacteriophages have a completely different antibacterial mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, by way of an example from personalized medicine, the treatment of bacterial infections in humans or animals is routinely based on the isolation of bacterial strains from the patient and isolation of specific phages for the respective pathogen [ 72 , 73 , 74 ]. This approach has shown promising results and demands for the regular update of phage cocktails in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…However, emergence of multidrug-resistant ‘superbugs’ has rekindled the interest in phage therapy. Studies have shown that phage therapy can be used as an alternative biocontrol agent or adjuvant therapy to antibiotics in human and animals (Petrovic Fabijan et al 2020 ; Schooley et al 2017 ; Ooi et al 2019 ; Waters et al 2017 ; Greene et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%